Anti-diabetic Potency and Characteristics of Probiotic Goat-Milk Yogurt Supplemented with Roselle Extract during Cold Storage - R. R. S. Wihansah; I. I. Arief; I. Batubara (Tropical Animal Science Journal, 2018)
This study aimed to evaluate the anti-diabetic potency by in vitro method and the characteristics of probiotic goat-milk yogurt supplemented with roselle extract during cold storage. The experiment used three treatments namely yogurt, probiotic yogurt, and probiotic yogurt supplemented with roselle extract. Yogurt was stored in cold storage (4 oC) and was evaluated for the characteristics and anti-diabetic potency on days 0, 5, 10, and 15. The anti-diabetic potency was analyzed by a-glucosidase inhibitory activity. The results showed that goat milk in this study had a good quality including fat, SNF, protein, lactose content, density, and freezing point. Roselle extract had anti-diabetic potency with 87.72% inhibition at 25% concentration and also had 13.64% IC50 value. The anti-diabetic potency was affected by the type of yogurt, storage duration, and their interaction (P<0.05). Viscosity and water activity were affected by storage duration (P<0.05), meanwhile titratable acidity and pH value were affected by the type of yogurt. Total lactic acid bacteria were affected by storage duration, and there was an interaction between the type of yogurt and storage duration. In conclusion, probiotic yogurt supplemented with roselle extract had the highest anti-diabetic potency among all treatments with 36.70% inhibition. The inhibitory activity of probiotic yogurt supplemented with roselle extract decreased during 15 days of cold storage. The inhibition was comparable with acarbose at 0.1-0.5 ppm concentration. Physical, chemical, and microbiological characteristics of yogurt in this study were good and could be consumed up to 15 days of cold storage.